THE DYNAMICS OF SCHOOL-COMMUNITY RELATIONS IN THE CONTEXT OF CULTURAL DIVERSITY AT SDN 007 LONG MESANGAT - nurngaini; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
This study aims to analyze the dynamics of the relationship between the school and the community in the context of cultural diversity at SDN 007 Long Mesangat. This study employs a qualitative approach using a case study design. Data collection techniques included observation, in-depth interviews, and documentation, involving the school principal, teachers, parents, and community leaders as research subjects. The results indicate that the relationship between the school and the community has not been functioning optimally, as evidenced by low community participation in school activities and a lack of communication and cooperation between the two parties. The main factors influencing this condition are economic factors, low awareness of the importance of education, time constraints, and differences in cultural backgrounds. The impact of this weak relationship is evident in the lack of support for students’ learning processes and the sub-optimal implementation of school programs. Therefore, strategic efforts are needed to enhance cooperation between the school and the community through flexible, educational, and locally-based cultural approaches to support educational success.